2020
DOI: 10.1002/bdr2.1759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interactive effects between paternal alcohol consumption and paternal socioeconomic status and environmental exposures on congenital heart defects

Abstract: Background: While the maternal risk factors on congenital heart defects (CHDs) have often been assessed, paternal contribution to CHDs, especially the joint effects of paternal risk factors on CHDs remain unknown. This study examined the major impacts of paternal alcohol consumption and its interaction (on multiplicative and additive scales) with paternal socioeconomic status (SES) and environmental exposures on CHDs in China. Methods: A population-based case-control study involving 4,726 singleton CHDs cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In recent years, substantial epidemiological evidence has demonstrated that non-genetic factors such as social determinants of health and adverse healthy lifestyle also contribute to abnormal cardiovascular development in fetuses, leading to cardiovascular malformation. The dominant factors of CHD could be divided into six main categories, namely (1) sociodemographic factors, including parental age (11,12), household annual income and education level (13); (2) adverse lifestyle (14); (3) maternal diseases, including pre-pregnancy diabetes (15) and fever (16); (4) environmental factors such as secondhand smoke exposure (17) and environmental pollution (18); (5) supplements such as folic acid and multivitamin (19); and (6) mode of conception (20). Previous research mainly focused on the association between limited predictors and the risk of CHD, and some conclusions involving maternal fever (16,21), maternal folic acid, and multivitamin supplementation (19,22,23) have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial epidemiological evidence has demonstrated that non-genetic factors such as social determinants of health and adverse healthy lifestyle also contribute to abnormal cardiovascular development in fetuses, leading to cardiovascular malformation. The dominant factors of CHD could be divided into six main categories, namely (1) sociodemographic factors, including parental age (11,12), household annual income and education level (13); (2) adverse lifestyle (14); (3) maternal diseases, including pre-pregnancy diabetes (15) and fever (16); (4) environmental factors such as secondhand smoke exposure (17) and environmental pollution (18); (5) supplements such as folic acid and multivitamin (19); and (6) mode of conception (20). Previous research mainly focused on the association between limited predictors and the risk of CHD, and some conclusions involving maternal fever (16,21), maternal folic acid, and multivitamin supplementation (19,22,23) have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%